2021
DOI: 10.1111/ijfs.15488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different crop starches on the cooking quality of Chinese dried noodles

Abstract: To investigate the effects of seven starches made from different crop sources on noodle quality, Chinese dried noodles made from various reconstituted flours were prepared and analysed. Potato starch had better solubility and swelling power than the other starches, leading to higher water absorption, cooking loss and breakage ratio of the potato starch noodles. The correlation results unravelled that the cooking breakage ratio of noodles presented positive correlations with solubility, swelling power, peak vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Compared with the CP, the more compact and less cracks and holes were found with decreasing the particle size. A similar phenomenon has also occurred in other noodles ( Li et al, 2022 ; Odabas et al, 2022 ; Wu et al, 2015 ; Xiang et al, 2018 ; Yang, Dhital, et al, 2021 ; Yang, Zhang, et al, 2021 ).…”
Section: Resultssupporting
confidence: 73%
“…Compared with the CP, the more compact and less cracks and holes were found with decreasing the particle size. A similar phenomenon has also occurred in other noodles ( Li et al, 2022 ; Odabas et al, 2022 ; Wu et al, 2015 ; Xiang et al, 2018 ; Yang, Dhital, et al, 2021 ; Yang, Zhang, et al, 2021 ).…”
Section: Resultssupporting
confidence: 73%
“…This is an important measure of starch properties. Analysis of starch in noodles with high swelling power indicated that more starch granules were swelling in such noodles (Li et al ., 2022). In the current study, the swelling power of starch in fermented dried noodles subjected to different drying conditions is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1). Soaking flour in alkaline solution resulted in swelling of starch granules due to disruption and removal of proteins on the surface of starch granules (Nadiha et al ., 2010; Li et al ., 2022). The negative charges on double‐helical regions of starch are converted to a single‐helical structure and the crystalline structure is destroyed (Jane & Seib, 1991) inducing starch granules to swell.…”
Section: Resultsmentioning
confidence: 99%
“…Swelling power of starch granule is influenced by several factors such as plant source, amylose content, protein content, starch modification method and their interaction (Yadav et al ., 2010; Li et al ., 2022). In this study, commercial rice flour and the two flour mixtures with limewater soaking treatment had significantly higher swelling power ( P ≤ 0.05) at 85 °C than their corresponding unsoaked samples (Fig.…”
Section: Resultsmentioning
confidence: 99%